Diverse molecular mechanisms of transcription regulation by the bacterial alarmone ppGpp. Issue 2 (25th December 2021) - Travis, Brady A.; Schumacher, Maria A.
Abstract: Bacteria must rapidly detect and respond to stressful environmental conditions. Guanosine tetraphosphate (ppGpp) is a universal stress signal that, in most bacteria, drives the reprograming of transcription at a global level. However, recent studies have revealed that the molecular mechanisms utilized by ppGpp to rewire bacterial transcriptomes are unexpectedly diverse. In Proteobacteria, ppGpp regulates the expression of hundreds of genes by directly binding to two sites on RNA polymerase (RNAP), one in combination with the transcription factor, DksA. Conversely, ppGpp indirectly regulates transcription in Firmicutes by controlling GTP levels. In this case, ppGpp inhibits enzymes that salvage and synthesize GTP, which indirectly represses transcription from rRNA and other promoters that use GTP for initiation. More recently, two different mechanisms of transcription regulation involving the direct binding of transcription factors by ppGpp have been described. First, in Francisella tularensis, ppGpp was shown to modulate the formation of a tripartite transcription factor complex that binds RNAP and activates virulence genes. Second, in Firmicutes, ppGpp allosterically regulates the transcription repressor, PurR, which controls purine biosynthesis genes. The diversity in bacterial ppGpp signaling revealed in these studies suggests the likelihood that additional paradigms in ppGpp‐mediated transcription regulation await discovery. Abstract : This review covers recent molecular mechanistic findings on how ppGpp rewires bacterial transcriptomes. The data reveal an unexpected diversity of mechanisms, which are compared and contrasted in this review.